INFLUENCE OF PROSTHETIC TREATMENT ON PATIENTS GENERAL HEALTH-CLINICAL STUDY - Dana Gabriela Budală; Zenaida Surlari; Dan Nicolae Bosînceanu; Florinel Cosmin Bida; Dragoș Ioan Virvescu; Elena Raluca Baciu (Romanian Dental Association for Education, 2022)
Prosthetic treatment, in general, has a significant impact on quality of life, with clinically relevant indicators and statistically verified effects over time. Material and methods: our research involved 172 patients who were treated with dental bridges, partial removable dentures, or complete removable dentures. Replacement of partially detachable and complete removable dentures that no longer matched the stomatognathic system's functionality, as well as the installation of new dental bridges, were among the treatments. Results: the results of the present study showed that the majority of patients initially assessed their dental health as moderate (36.3 percent) or good (48.6%), whereas their overall health was rated as superior (56.4%).